The association of Curcuma and Scutellaria plant extracts improves laying hen thermal tolerance and egg oxidative stability and quality under heat stress conditions - Giannenas, Ilias; Sakkas, Panagiotis; Papadopoulos, Georgios A.; Mitsopoulos, Ioannis; Stylianaki, Ioanna; Dokou, Stella; Tsiouris, Vasileios; Papagrigoriou, Theodora; Panheleux, Marina; Robert, Fabrice; Bampidis, Vasileios A. (Frontiers in Veterinary Science, 2022)
Chronic exposure to high ambient temperatures is detrimental to laying hen performance and egg quality. Plant secondary metabolites may alleviate effects, partly due to their antioxidant activities. Herein, we investigated the effects of dietary supplementation with a phytonutrient solution (PHYTO) consisting of a plant extract combination of Scutellaria baicalensis and Curcuma longa on young layers (25–32 wk of age) raised under naturally elevated temperature conditions. Four hundred, 24-wk-old Lohmann hens were allocated in 50 cages and, after a week of adaptation, were offered a diet either containing 2 g/kg of PHYTO or not, for 8 wk. Hen BW was measured at the beginning and end of the trial, and egg production and feed intake were recorded weekly. At week 32, four eggs per cage were collected to determine egg quality characteristics as well as the rate of lipid and albumen oxidation in fresh eggs. At the end of the trial, two hens per cage were blood sampled for assessment of biochemical markers, one of which was euthanized for histopathological evaluation of the liver and intestine and assessment of intestinal histomorphometry. The herbal mixture supplementation significantly increased egg production rate at weeks 28 and 29 and for the overall production period, and feed efficiency at weeks 26–29. In addition, the degree of liver necrosis and microvascular thrombosis was lower (P < 0.05) whereas intestinal villosity was greater in duodenal and jejunal segments (P < 0.05) in the PHYTO compared to the control group. Supplementation also reduced (P < 0.05) blood concentrations of corticosterone, alanine aminotransferase activity, and TBARS, and a reduction in catalase activity was observed. Egg quality characteristics were not affected, except for eggshell thickness, egg diameter, and eggshell breaking strength that were superior in the PHYTO group (P < 0.05). PHYTO supplementation significantly improved egg lipid oxidation status of fresh eggs. In conclusion, supplementation with PHYTO improved laying hen productivity and egg quality, which was associated with an improvement in laying hen thermotolerance.